On solution of the integral equations for the potential problems of two circular-strips - C. Sampath; D. L. Jain (International Journal of Mathematics and Mathematical Sciences)
Solutions are given to some singular integral equations which arise in two-dimensional Dirichlet and Newmann boundary value problems of two equal infinite coaxial circular strips in various branches of potential theory. For illustration, these solutions are applied to solve some boundary value problems in electrostatics, hydrodynamics, and expressions for the physical quantities of interest are derived.